Bioethanol (Biofuel) Production from Low Grade Dates - Ali Abbas, Raghad; M. Flayeh, Hussain (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
Bioethanol production from sugar fermentation is one of the most sustainable alternatives to substitute fossil fuel. production of bioethanol from low grade dates which are rich of sugars. An available sugar from a second grade dates (reduction sugar) was 90g/l in this study. Sugar can be served as essential carbon sources for yeast growth in aerobic condition and can also be converted to bioethanol in anaerobic condition. The effect of various parameters on bioethanol production, fermentation time, pH-values, inoculum size and initial sugar concentration were varied in order to determine the optimal of bioethanol production. The highest bioethanol yield was 33g/l which was obtained with sugar concentration 90 g/l, inoculum size 1%, 52h time and pH-value 5.